Phosphorene, antimonene, silicene and siloxene based novel 2D electrode materials for supercapacitors - A brief review - Venkateshalu, Sandhya; Subashini, G.; Bhardwaj, Preetam; Jacob, George; Sellappan, Raja; Raghavan, Vimala; Jain, Sagar M.; Pandiaraj, Saravanan; Natarajan, Varagunapandiyan; Al Alwan, Basem Abdullah M.; Al Mesfer, Mohammed Khaloofah Mola; Alodhayb, Abdullah; et al. (Elsevier, 2022)
In the past decade, 2D materials such as graphitic carbon nitride, transition metal dichalcogenides, layered metal oxides and hydroxides, hexagonal boron nitride and MXenes have garnered a great attention with the discovery of graphene. Very recently, novel 2D materials analogous to graphene such as phosphorene, antimonene, silicene, siloxene, germanene etc., were discovered and are emerging as strong competitors to the existing 2D materials. These materials pose explicit properties making them suitable for various applications. This article reviews the properties, synthesis techniques and the supercapacitive nature of phosphorene, antimonene, silicene and siloxene while briefing the properties of other 2D materials viz. germanene, stanene, arsenene and bismuthene. With the successful implementation of phosphorene as supercapacitor electrode, research is progressing in exploring the supercapacitive nature of other novel 2D materials. The investigations on these materials are still in its infancy and most of the properties lack experimental evidence. The current research trends on these novel materials are discussed in this review.
Keywords: 2D materials; Graphene; Phosphorene; Antimonene; Supercapacitors